Risk factors for brain metastasis as a first site of disease recurrence in patients with HER2 positive early stage breast cancer treated with adjuvant trastuzumab. (February 2016) - Tonyali, Onder; Coskun, Ugur; Yuksel, Sinemis; Inanc, Mevlude; Bal, Oznur; Akman, Tulay; Yazilitas, Dogan; Ulas, Arife; Kucukoner, Mehmet; Aksoy, Asude; Demirci, Umut; Uysal, Mukremin; et al.
Abstract: Purpose: The aim of this study was to determine risk factors for brain metastasis as the first site of disease recurrence in patients with HER2-positive early-stage breast cancer (EBC) who received adjuvant trastuzumab. Methods: Medical records of 588 female patients who received 52-week adjuvant trastuzumab from 14 centers were evaluated. Cumulative incidence functions for brain metastasis as the first site of disease recurrence and the effect of covariates on brain metastasis were evaluated in a competing risk analysis and competing risks regression, respectively. Results: Median follow-up time was 36 months. Cumulative incidence of brain metastasis at 12 months and 24 months was 0.6% and 2%, respectively. HER2-enriched subtype (ER− and PR−) tumor ( p = 0.001, RR: 3.4, 95% CI: 1.33–8.71) and stage 3 disease ( p = 0.0032, RR: 9.39, 95% CI: 1.33–8.71) were significant risk factors for development of brain metastasis as the first site of recurrence. Conclusions: In patients with HER2 positive EBC who received adjuvant trastuzumab, HER2-enriched subtype (ER− and PR−) tumor and stage 3 disease were associated with increased risk of brain metastasis as the first site of disease recurrence.